Analisis Dinamika Atmosfer Kejadian Hujan Lebat Di Surabaya 30 Maret 2023 - Cekarus, Joseph Damian; Muhammad Ariel Taufik Muharram; Yosafat Donni Haryanto (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2025)
On March 30, there was heavy rain with an intensity of 25 mm/hour. Heavy rains are caused by cumulonimbus convective cloud activity. This cloud activity can be analyzed by utilizing Himawari-8 satellite remote sensing with RGB, CCO, and using the upper air observation method with radiosonde at 00 UTC in the Surabaya area. The purpose of this research is to identify heavy rain in some areas of Surabaya according to some news in the area. The results of observations from the RGB method occurred cloud conditions resulting in high heavy rain. The observation results of the CCO method occurred convective clouds at the time of the heavy rain event with high intensity. The results of observations of upper air observations with radiosonde at 00 UTC showed an atmospheric stability index indicating a chance of extreme weather in the Surabaya area. In addition, based on ECMWF Copernicus reanalysis data, there is a warm and humid airflow from the Java Sea to the mainland which causes cloud formation and heavy rain. In addition, a negative value of divergence is obtained and the humidity value reaches 80%. This shows that the analysis using the RGB method, CCO, radiosonde data, and Copernicus ECMWF reanalysis data are compatible and support each other.